Introduction to digital communication. - Ziemer, Rodger E., ....-; Peterson, Roger L., ....- (Upper Saddle River : Prentice Hall, 2001)
1. Introduction to Digital Data Transmission. 2. Signals, Systems, Modulation and Noise- Overview. 3. Basic Digital Communication Systems. 4. Signal-Space Methods in Digital Data Transmission. 5. Channel Degradations in Digital Communications. 6. Fundamentals of Information Theory and Block Coding. 7. Fundamentals of Convolutional Coding. 8. Fundamentals of Repeat Request Systems. 9. Spread-Spectrum Systems. 10. Introduction to Cellular Radio Communications. 11. Satellite Communications. Appendix A. Probability and Random Variables, Appendix B. Characterization of Internally Generated Noise. Appendix C. Attenuation of Radio-Wave Propagation by Atmospheric Gases and Rain. Appendix D. Generation of Coherent References. Appendix E. Gaussian Probability Function. Appendix F. Mathematical Tables. Subject Index.
Keywords: Digitale communicatie